Daylight entanglement-based quantum key distribution with a quantum dot source. (1st April 2023) - Basso Basset, F; Valeri, M; Neuwirth, J; Polino, E; Rota, M B; Poderini, D; Pardo, C; Rodari, G; Roccia, E; Covre da Silva, S F; Ronco, G; Spagnolo, N; et al.
Abstract: Entanglement-based quantum key distribution can enable secure communication in trusted node-free networks and over long distances. Although implementations exist both in fiber and in free space, the latter approach is often considered challenging due to environmental factors. Here, we implement a quantum communication protocol during daytime for the first time using a quantum dot source. This technology presents advantages in terms of narrower spectral bandwidth—beneficial for filtering out sunlight—and negligible multiphoton emission at peak brightness. We demonstrate continuous operation over the course of three days, across an urban 270 m-long free-space optical link, under different light and weather conditions.